Gambaran Pengetahuan Ibu Hamil Tentang Perdarahan Postpartum - Sri Purnama Alam; Sukmawati; Nina Sumarni (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
The maternal mortality rate in West Java in 2018 was still high while in Garut Regency was second rank after Indramayu. The highest cause of maternal death is post partum hemmorage, one of the efforts to prevent post hemmorage by conducting routine ANC and Family Planning. Good knowledge is needed to prefered birthing and anticipate if there is post partum hemmorage. The purpose of this research was to determine the description of pregnant women's knowledge level about post partum hemmorage.This type of research used quantitative descriptive. The population in this research were all pregnant women who visited Cilawu Health Center with sample of 111 people. Sampling used the accidental sampling technique. The instrument in this research adopted from previous researchers which was modified by the researcher and tested for validity and reliability in Cimaragas Health Center with validity test result r count = 0.473-0.663 and reliability result = 0.885. The variables in this study are pregnant women’s knowledge about post partum hemmorage with a level of C2 comprehension. Analysis used univariate with frequency distribution percentage .The result showed that the knowledge of pregnant women was almost half in the category of sufficient knowledge (44.1%), small portion was in the category of insufficient knowledge (17.1%) and nearly half were in the category of good knowledge (38.7%). The conclusion from the result of the research showed that the description of pregnant women's knowledge level about post partum hemmorage nearly half of them had sufficient knowledge. It is hoped that health workers will more intensively provide health education about post partum hemmorage, especially for pregnant women who are at risk.